2022
DOI: 10.1021/acs.jafc.1c08137
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CYP76C6 Facilitates Isoproturon Metabolism and Detoxification in Rice

Abstract: Agricultural chemical residues in farmland and crops is one of the serious public issues that constantly threatens crop production, food security, and human health. Understanding their decay mechanism in crops for accelerating their degradative metabolism is important. In this study, a rice uncharacterized cytochrome P450 gene encoding CYP76C6 was functionally identified in rice exposed to isoproturon (IPU). To verify the role of CYP76C6 in rice resistance to IPU toxicity, CYP76C6 overexpression (OEs) and knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…For instance, LOC_Os08g39730 ( CYP76C6 ) is the P450 gene with the highest expression in shoots and roots under the two DU concentrations (Figure ). The overexpression of CYP76C6 in rice was verified to attenuate the toxicity of phenylurea herbicides isoproturon (IPU) via the increments of metabolite contents, such as C -hydroxylated IPU and N -demethylated IPU . In addition, LOC_Os01g43710 encoding CYP72A18, a rice cytochrome P450 that catalyzes (ω-1)-hydroxylation of the herbicide pelargonic acid, was found to be higher transcription by 1.17-, 2.56-, 2.88-, and 3.05-fold in shoots and roots of rice under two concentrations of DU treatment.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…For instance, LOC_Os08g39730 ( CYP76C6 ) is the P450 gene with the highest expression in shoots and roots under the two DU concentrations (Figure ). The overexpression of CYP76C6 in rice was verified to attenuate the toxicity of phenylurea herbicides isoproturon (IPU) via the increments of metabolite contents, such as C -hydroxylated IPU and N -demethylated IPU . In addition, LOC_Os01g43710 encoding CYP72A18, a rice cytochrome P450 that catalyzes (ω-1)-hydroxylation of the herbicide pelargonic acid, was found to be higher transcription by 1.17-, 2.56-, 2.88-, and 3.05-fold in shoots and roots of rice under two concentrations of DU treatment.…”
Section: Resultsmentioning
confidence: 94%
“…These metabolic processes were divided into four phases, according to the types of enzyme-catalyzed reactions . In Phase I, cytochrome P450s, hydrolase, esterase, and monooxygenase are responsible for the dealkylation, hydroxylation, and dehalogenation of intermediates in plants, which is considered to be the first step of xenobiotic detoxification . Plant cytochrome P450s belonging to the largest family of enzymatic proteins have been found to participate in mediating the metabolism of xenobiotics or herbicides .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, soybean, an economic crop, can fix nitrogen via symbiosis to reduce the need for synthetic fertilizers. IPU can exhibit toxicities to non‐target plants, such as preventing root and leaf growth, reducing chlorophyll content, and inhibiting photosynthetic efficiency (Yin et al ., 2008 ; Zhai et al ., 2022 ). In our study, TS soybeans expressing the bacterial N‐ demethylase PdmAB showed improved IPU tolerance than non‐TS soybeans (Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%